2010
DOI: 10.1371/journal.pone.0011986
|View full text |Cite
|
Sign up to set email alerts
|

The Chemokine CXCL13 Is a Prognostic Marker in Clinically Isolated Syndrome (CIS)

Abstract: BackgroundThere is increasing recognition of the importance of B lymphocytes in the immunopathogenesis of multiple sclerosis (MS), encouraging the evaluation of B cell-associated biomarkers in the cerebrospinal fluid (CSF). We aimed to evaluate the relevance of the B cell chemoattractant CXCL13 as a prognostic marker in patients with clinically isolated syndrome (CIS) regarding conversion to MS, and to compare it to Barkhof criteria in magnetic resonance imaging (MRI), oligoclonal bands (OCB) and the polyspeci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

11
99
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(115 citation statements)
references
References 42 publications
(68 reference statements)
11
99
1
2
Order By: Relevance
“…In conjunction with demonstrations that the circulating B cells of patients with IPF are not uniquely ORIGINAL ARTICLE deficient in their expression of the chemotactic ligand CXCR5 (Figure 2), and numerous definitive reports in other populations (31)(32)(33)(34)(35)(36), it is thus highly likely the CXCL13-CXCR5 axis is involved in the focal accumulations of nonproliferating B cells that were found in IPF lungs here and in other studies (3)(4)(5) Figure 4). The longitudinal CXCL13 assays here ( Figure 5) support the validity of these cross-sectional observations.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…In conjunction with demonstrations that the circulating B cells of patients with IPF are not uniquely ORIGINAL ARTICLE deficient in their expression of the chemotactic ligand CXCR5 (Figure 2), and numerous definitive reports in other populations (31)(32)(33)(34)(35)(36), it is thus highly likely the CXCL13-CXCR5 axis is involved in the focal accumulations of nonproliferating B cells that were found in IPF lungs here and in other studies (3)(4)(5) Figure 4). The longitudinal CXCL13 assays here ( Figure 5) support the validity of these cross-sectional observations.…”
Section: Discussionsupporting
confidence: 79%
“…The findings in these subjects with IPF parallel analogous observations in patients with other syndromes that are known to be mediated by pathologic B cells (31)(32)(33). Given the lack of progress in the treatment of IPF, which remains a highly morbid and almost invariably fatal disease (1), objective considerations of pathogenic paradigms that could illuminate new therapeutic approaches for this disease seem warranted.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…CXCL13 is produced by stromal cells and influences the migration of B cells (12). Previous studies have shown elevated concentrations of CXCL13 in the CSF samples of patients with Lyme neuroborreliosis, multiple sclerosis, and some other inflammatory diseases (11,(13)(14)(15)(16), suggesting that CXCL13 is a diagnostic marker for Lyme neuroborreliosis (17,18). As has been indicated by some reports, elevated concentrations of CXCL13 in the CSF may appear several days before intrathecal borrelial antibody synthesis occurs (18,19).…”
mentioning
confidence: 85%